Genome‐wide association study of alcohol use disorder identification test (AUDIT) scores in 20 328 research participants of European ancestry. (23rd October 2017) - Sanchez‐Roige, Sandra; Fontanillas, Pierre; Elson, Sarah L.; ,; Gray, Joshua C.; de Wit, Harriet; Davis, Lea K.; MacKillop, James; Palmer, Abraham A.
Abstract: Genetic factors contribute to the risk for developing alcohol use disorder (AUD). In collaboration with the genetics company 23andMe, Inc., we performed a genome‐wide association study of the alcohol use disorder identification test (AUDIT), an instrument designed to screen for alcohol misuse over the past year. Our final sample consisted of 20 328 research participants of European ancestry (55.3% females; mean age = 53.8, SD = 16.1) who reported ever using alcohol. Our results showed that the 'chip‐heritability' of AUDIT score, when treated as a continuous phenotype, was 12%. No loci reached genome‐wide significance. The gene ADH1C, which has been previously implicated in AUD, was among our most significant associations (4.4 × 10 −7 ; rs141973904). We also detected a suggestive association on chromosome 1 (2.1 × 10 −7 ; rs182344113) near the gene KCNJ9, which has been implicated in mouse models of high ethanol drinking. Using linkage disequilibrium score regression, we identified positive genetic correlations between AUDIT score, high alcohol consumption and cigarette smoking. We also observed an unexpected positive genetic correlation between AUDIT and educational attainment and additional unexpected negative correlations with body mass index/obesity and attention‐deficit/hyperactivity disorder. We conclude that conducting a genetic study using responses to an online questionnaire in a population not ascertained for AUD may represent a cost‐effective strategy for elucidating aspects of the etiology of AUD. Abstract : We performed a genome‐wide association study of the Alcohol Use Disorder Identification Test (AUDIT) using 20 328 research participants of European ancestry. No loci reached genome‐wide significance. An SNP near the gene ADH1C was among our most significant associations (4.4 × 10 −7 ; rs141973904); this locus has been previously implicated in both alcoholism and alcohol consumption. We identified positive genetic correlations between AUDIT and multiple traits, including alcohol consumption and smoking initiation.